2022
DOI: 10.1021/acs.est.2c02189
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Mineral Phase Evolution and Arsenic Retention in Microfluidic Models of Zerovalent Iron-Based Water Treatment

Abstract: Arsenic (As) is a toxic element, and elevated levels of geogenic As in drinking water pose a threat to the health of several hundred million people worldwide. In this study, we used microfluidics in combination with optical microscopy and X-ray spectroscopy to investigate zerovalent iron (ZVI) corrosion, secondary iron (Fe) phase formation, and As retention processes at the pore scale in ZVI-based water treatment filters. Two 250 μm thick microchannels filled with single ZVI and quartz grain layers were operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…A recent study has shown that intermitted flow without exposure to air leads to the formation of mixed Fe(II,III) phases and magnetite, which are denser than Fe(III) phases and thus maintain better porosity in the filter and higher corrosion rates. 60 Figure 2 shows an old filter with the outlet lower than the nail bed (red) and a filter filled with new nails and sand and a raised outlet (green).…”
Section: Improved As Removal With Adapted Filtersmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study has shown that intermitted flow without exposure to air leads to the formation of mixed Fe(II,III) phases and magnetite, which are denser than Fe(III) phases and thus maintain better porosity in the filter and higher corrosion rates. 60 Figure 2 shows an old filter with the outlet lower than the nail bed (red) and a filter filled with new nails and sand and a raised outlet (green).…”
Section: Improved As Removal With Adapted Filtersmentioning
confidence: 99%
“…Formation of denser mixed Fe(II,III) phases and particularly of magnetite in constantly immersed nail beds can maintain a better permeability. 60,61 A slightly higher TDS in the postmonsoon season is indicative of an increased water−rock interaction during high-precipitation seasons and caused by an increased particle size in the groundwater: such particles can also lead to a decline in the porosity of the nail bed and subsequent clogging.…”
Section: Improved As Removal With Adapted Filtersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, whatever the speed at which spectra are acquired, the signal-to-noise ratio of the spectra represents a real limitation, and in all cases, the sample is constantly evolving during acquisition. The integration of microfluidic chips with XAS has emerged as a promising approach, opening up new avenues for studying, in situ and operando, chemical, physicochemical, and biological systems on a microscale. Indeed, there has been recently an increasing use of microfluidic cells in environmental applications as water treatment, carbon storage, phosphate immobilization, etc . These miniaturized experimental devices, commonly referred to as “laboratories on chips,” offer ideal microplatforms to study complex reaction kinetics, diffusion phenomena, and reaction mechanisms under controlled flow conditions, such as mixing, diffusion, and concentration gradients .…”
Section: Introductionmentioning
confidence: 99%